2018
DOI: 10.3390/ma11020293
|View full text |Cite
|
Sign up to set email alerts
|

Progress and Challenges of Ultrasonic Testing for Stress in Remanufacturing Laser Cladding Coating

Abstract: Stress in laser cladding coating is an important factor affecting the safe operation of remanufacturing components. Ultrasonic testing has become a popular approach in the nondestructive evaluation of stress, because it has the advantages of safety, nondestructiveness, and online detection. This paper provides a review of ultrasonic testing for stress in remanufacturing laser cladding coating. It summarizes the recent research outcomes on ultrasonic testing for stress, and analyzes the mechanism of ultrasonic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…However, there are some micro defects (pores and cracks) in SLM 316L stainless steel parts [5,6] that affect the bearing capacity of the part under fatigue loading. Traditional NDT technologies (such as X-ray [7,8], ultrasound [9][10][11], eddy current [12,13], penetrant [14,15], and magnetic powder [16]) have limitations in the detection of micro defects. Classical nonlinear acoustics theory shows that second harmonics are mainly induced by a harmonicity of the crystal lattice of materials [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are some micro defects (pores and cracks) in SLM 316L stainless steel parts [5,6] that affect the bearing capacity of the part under fatigue loading. Traditional NDT technologies (such as X-ray [7,8], ultrasound [9][10][11], eddy current [12,13], penetrant [14,15], and magnetic powder [16]) have limitations in the detection of micro defects. Classical nonlinear acoustics theory shows that second harmonics are mainly induced by a harmonicity of the crystal lattice of materials [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…It provides a new option to repair damaged parts, especially important parts, greatly reducing cost and enhancing work efficiency [8]. LC repair technology is a kind of remanufacturing technology, which repairs damaged parts and components using reverse engineering and powder-feed additive manufacturing [9,10]. LC repair has multiple advantages: low heat input leads to low distortion and low thermal damage in the base substrate, wide material applicability, rapid response to market demand, and a finer microstructure achieved, compared to arc welding, cold spray, and plasma spray [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Laser cladding technology is an advanced surface modification technology, which involves many disciplines, such as metal materials, metallurgy, Symmetry 2020, 12, 1126 2 of 11 chemistry, and so on. It is found that the tensile strength and hardness of the coating are always higher than that of the substrate, and the performance is better than that of the substrate [4][5][6][7], no matter how the laser power is set in a certain range. However, the analysis of the effect of friction heat on the wear resistance of laser cladding materials remains to be discussed.…”
Section: Introductionmentioning
confidence: 99%